IMPLEMENTASI METODE BEKESAH PADA ANAK MELAYU SAMBAS - Asyruni Multahada (Cross-border, 2019)
The bekesah or storytelling method is a method that can be used to internalize the values of early childhood education. Parents and the public must understand and know that preserving the bekesah method can have a positive impact on the development of children's character, and can maintain the existence of culture, such as folklore in the current era of modernization. Preserving folklore through the bekesah method can be done verbally (spoken), or story books. However, there are very few books on folklore, especially from the Sambas area, so they need to be redeveloped. Now folk tales have also been released into a song, such as the song Batu Ballah and the song Datok Kulub which is a Sambas folk song.